Personality of a Good Language Learner: a Case Study in EFL Context - Amalia, Puji Astuti; Aridah, Aridah (Universitas Islam Negeri Walisongo Semarang, 2021)
This case study aims to explore how the personality traits of a good language learner contributed to her success in language learning. Using a case study design, this study involved one student who met the criteria of a good language learner who became a champion of English competitions. This study used the Myers-Briggs Type Indicator personality test and semi-structured interviews to collect the data. The study showed that Meta's extrovert personality was described as talkative, confident, enthusiastic, and assertive. She understood a problem by talking about it and heard others' ideas in solving problems. As a sensing personality, she was objective and made decisions based on logic and facts to decide both sides. As a thinking person, she always worked with plans, and in making plans, she analyzed the pros and cons. She was objective and consistent in doing what she had planned. Her judging personality described how she dealt with their outer world. She had a decided lifestyle that had helped her achieve her goals in language learning by planning her language learning activities.